Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru SMP Negeri 3 Bireuen - Munawar Munawar; Jalaluddin Jalaluddin (Yayasan Hurriah, Banda Aceh, 2021)
English: The principal plays a key role in improving and building responsibility, discipline, and commitment of teachers. Based on these ideas, the focus of this research is how the leadership of school principals in improving teacher performance in SMP Negeri 3 Bireuen. This study aims to get an overview of the principal efforts in increasing responsibility, discipline and commitment in improving the performance of teachers at Junior High School 3 Bireuen. This study used a qualitative descriptive approach. Data collected through observation and interviews. The subject of this research is the principal and teacher councils. The results showed that the principal's leadership SMP Negeri 3 Bireuen in improving teacher performance more encouragement and providing necessary facilities. The principal is very little to do training and coaching to improve teacher performance. Efforts to increase the responsibility and discipline of teachers, principals do with providing guidance, supervision, and disciplinary actions in the teaching-learning process. Meanwhile, to improve the school's head teacher's commitment to send teachers to follow the upgrading of teachers and involve teachers in consultation activities subjects (MGMP). Bahasa: Kepala sekolah memegang peranan penting dalam upaya peningkatan dan pembinaan terhadap tanggung jawab, disiplin, dan komitmen guru. Berdasarkan pemikiran tersebut, fokus penelitian ini adalah bagaimana kepemimpinan kepala sekolah dalam meningkatkan kinerja guru pada SMP Negeri 3 Bireuen. Penelitian ini bertujuan untuk mendapatkan gambaran tentang upaya kepala sekolah dalam meningkatkan tanggung jawab, disiplin dan komitmen dalam meningkatkan kinerja guru pada SMP Negeri 3 Bireuen. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui observasi dan wawancara. Subjek penelitian ini adalah kepala sekolah dan dewan guru. Hasil penelitian menunjukkan bahwa kepemimpinan kepala sekolah SMP Negeri 3 Bireuen dalam meningkatkan kinerja guru lebih banyak memberikan dorongan dan menyediakan sarana yang dibutuhkan. Kepala sekolah sangat sedikit melakukan pelatihan dan pembinaan untuk meningkatkan kinerja guru. Upaya untuk meningkatkan tanggung jawab dan disiplin guru, kepala sekolah melakukan dengan memberikan pembinaan, pengawasan, dan tindakan dalam disiplin pada proses belajar mengajar. Sedangkan untuk meningkatkan komitmen guru kepala sekolah mengirim guru untuk mengikuti penataran dan melibatkan guru dalam kegiatan musyawarah guru mata pelajaran (MGMP).